Estrogen Receptor, Progesterone Receptor, and Her-2/neu Oncogene Expression in Breast Cancers Among Bangladeshi Women - Mostafa, MG; Larsen, MT; Love, RR (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Two-thirds of all women who develop breast cancer each year live in Asia. In many countries, including Bangladesh, there are few data on the pathological characteristics of breast tumours. The objectives of this study were a) to describe the estrogen receptor (ER), progesterone receptor (PR), and the expression of Her-2/neu oncogene expression status in a large series of breast cancers occurring in Bangladeshi women and b) to correlate these findings with the patients' age at diagnosis, tumour histological grade, and presence of axillary lymph node metastatic disease. Method: One thousand forty two cases were evaluated in a referral practice. Tumour sections were stained immunohistochemically using Dako 1D5 (ER) and Dako 636 (PR) and semiquantitatively scored for ER and PR expression. Three hundred thirty five of these cases were also stained using Dako c-erb2 oncoprotein and scored for Her-2/neu over-expression. Results: Estrogen Receptor expression was positive in 69.0%, PR expression was positive in 72.3%, and Her-2/ neu was over-expressed (IHC score 3+) in 28.4% of the cases. Her-2/neu over-expression did not consistently correlate with ER and PR expression. ER and PR expression were inversely associated with tumour histological grade. Cases with axillary lymph node metastases had higher rates of ER and PR expression. No significant association was observed with patient’s age. Conclusion: Estrogen Receptor, PR, and Her-2/neu expression frequencies and prognostic factor associations in Bangladeshi women with breast cancer referred for tumour marker testing are very similar to those reported in Western countries. These findings have important implications for ensuring optimal testing capacity for all patients with these tumours, to allow for appropriate choices of treatment. DOI: 10.3329/jbcps.v28i3.6509 J Bangladesh Coll Phys Surg 2010; 28: 157-162